Occupational Safety and Health of Posted Workers - Rogelja, Nataša; Toplak, Kristina (ZRC SAZU, Založba ZRC, 2017)
The papers contained in this booklet were presented at the transnational conference "Employment/Working Conditions, Occupational Safety and Health of Posted Workers" in Ljubljana, Slovenia (15 February 2017). The conference brought together experts (researchers and practitioners) from several European countries to discuss the existing and new challenges related to OSH (occupational safety and health), labour, and working conditions of posted workers. The conference served as the launch event of the POOSH project, financed by the European Comission (Programme EaSI PROGRESS) and led by Dr. Kristina Toplak from the Slovenian Migration Institute at ZRC SAZU. The booklet is covering the topic of the OSH of posted workers from several angles. The first part is framed around contributions given by researchers working in the field of labor mobility, with the focus on the occupational safety and health of posted workers. The second part contains contributions from practitioners working in NGOs, trade unions or Ministries of Labour who presented their work as well as discussed national and transnational legislations related to the OSH of posted workers.